Correlation between presence of bacillus species and OHI-s in recurrent aphthous stomatitis patients - Carabelly, Amy Nindia; Apriasari, Maharani Lallyza; Dwipura, Irnamanda; Pramitha, Selviana Rizky; Sutanti, Viranda; Kurniasari, Annisa; Nafisah, Riznasyarielia Nikmatun (Universitas Padjadjaran, 2022)
ABSTRACTIntroduction: The approximate prevalence of Recurrent Aphthous Stomatitis (RAS) was 45.42% at Gusti Hasan Aman Dental Hospital Banjarmasin. Bacillus sp. is a bacterium that can form spores that can be transmitted through air, dust, water and food. Poor oral conditions will increase the possibility of bacterial contamination, especially for ulcers found in RAS. This study aimed to analyzed correlation between the presence of Bacillus species and OHI-S in the oral ulceration of RAS patients. Methods: This was an analytical cross-sectional study conducted among Oral Medicine Department outpatients at Gusti Hasan Aman Dental Hospital, Banjarmasin, Indonesia. A total of 38 subjects were examined to assess Oral Hygiene Index Simplified and obtained bacteria samples using the swabs technique. Bacteria were then inoculated in blood agar base media and concurrently presented with gram staining. Bacteria were then identified using the catalase test, urease test, and oxidase test. Results: Bacillus species were predominantly identified in oral ulceration of RAS patients at Gusti Hasan Aman Dental Hospital Banjarmasin. Bacillus sp. (60,5%), Streptococcus sp. (34,2%), Neisseria sp. (2,6%), and Lactobacillus sp. (2,6%) were found in ulcerated RAS lesions. Spearman test resulted in p = 0.862 (p > 0.05), where no significant difference was obtained between presence of bacillus species and OHI-s in recurrent aphthous stomatitis patients. Conclusion: Bacillus species were predominantly identified in oral ulceration of RAS patients a. However, the presence of Bacillus sp. was not associated with OHI-S in RAS patients.Keywords: bacillus sp.; oral hygiene index simplified; recurrent aphthous stomatitis